-5t-2(-5t+10)=100

Simple and best practice solution for -5t-2(-5t+10)=100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5t-2(-5t+10)=100 equation:


Simplifying
-5t + -2(-5t + 10) = 100

Reorder the terms:
-5t + -2(10 + -5t) = 100
-5t + (10 * -2 + -5t * -2) = 100
-5t + (-20 + 10t) = 100

Reorder the terms:
-20 + -5t + 10t = 100

Combine like terms: -5t + 10t = 5t
-20 + 5t = 100

Solving
-20 + 5t = 100

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 5t = 100 + 20

Combine like terms: -20 + 20 = 0
0 + 5t = 100 + 20
5t = 100 + 20

Combine like terms: 100 + 20 = 120
5t = 120

Divide each side by '5'.
t = 24

Simplifying
t = 24

See similar equations:

| -8(-8-6)=-6-22 | | 4x-5=5x-7 | | 12=-6z-6 | | x^3+13=-14 | | -5(9+a)=10 | | 44=t-20 | | 383=8x+7 | | 9=4(5-a) | | 10x+6=6x-3 | | -1(x+8)+9=7x+1-8x | | 2z=19.9 | | -11-5=6(5+4) | | -12=-2p+8 | | 12(3x-7)=-300 | | 2q=3 | | 3q+7=7q | | 0=6x+8 | | (X+0.2)(X+1.5)=0 | | 7q^2-9q-(n+2)=0 | | -4n+9=-7 | | -14+28=-2(x+6) | | 3x=360/4 | | 5(x+12)+7=11 | | 329-9x=14 | | g(20)=210-20(20) | | f(20)=210-20(20) | | (3x+2)(7x-4)=21x^2+10 | | (X-6)+y=12 | | f(20)=330-30(20) | | 15m+0.50=0.25+25m | | 92+(38)= | | 10-n=1-10n |

Equations solver categories